Answer:
61
Step-by-step explanation:
Let's find the points
and
.
We know that the
-coordinates of both are
.
So let's first solve:
![3=4x^2+x-1](https://tex.z-dn.net/?f=3%3D4x%5E2%2Bx-1)
Subtract 3 on both sides:
![0=4x^2+x-1-3](https://tex.z-dn.net/?f=0%3D4x%5E2%2Bx-1-3)
Simplify:
![0=4x^2+x-4](https://tex.z-dn.net/?f=0%3D4x%5E2%2Bx-4)
I'm going to use the quadratic formula,
, to solve.
We must first compare to the quadratic equation,
.
![a=4](https://tex.z-dn.net/?f=a%3D4)
![b=1](https://tex.z-dn.net/?f=b%3D1)
![c=-4](https://tex.z-dn.net/?f=c%3D-4)
![\frac{-1 \pm \sqrt{1^2-4(4)(-4)}}{2(4)}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%20%5Cpm%20%5Csqrt%7B1%5E2-4%284%29%28-4%29%7D%7D%7B2%284%29%7D)
![\frac{-1 \pm \sqrt{1+64}}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%20%5Cpm%20%5Csqrt%7B1%2B64%7D%7D%7B8%7D)
![\frac{-1 \pm \sqrt{65}}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%20%5Cpm%20%5Csqrt%7B65%7D%7D%7B8%7D)
Since the distance between the points
and
is horizontal. We know this because they share the same
.This means we just need to find the positive difference between the
-values we found for the points of
and
.
So that is, the distance between
and
is:
![\frac{-1+\sqrt{65}}{8}-\frac{-1-\sqrt{65}}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%2B%5Csqrt%7B65%7D%7D%7B8%7D-%5Cfrac%7B-1-%5Csqrt%7B65%7D%7D%7B8%7D)
![\frac{-1+\sqrt{65}+1+\sqrt{65}}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B-1%2B%5Csqrt%7B65%7D%2B1%2B%5Csqrt%7B65%7D%7D%7B8%7D)
![\frac{2\sqrt{65}}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B2%5Csqrt%7B65%7D%7D%7B8%7D)
![\frac{\sqrt{65}}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%7B65%7D%7D%7B4%7D)
If we compare this to
, we should see that:
.
So
.